ENHANCING SYNTHESIS AND EVALUATION SKILLS USING RECIPROCAL METHOD FOR ARABIC READING COMPREHENSION - Wangsadanureja, Miftah; Nurrudin, Nuruddin; Rahmat, Aceng (Arabi : Journal of Arabic Studies, 2019)
Arabic text reading is one of the subjects taught in the Mahad Huda Islami (MHI) Islamic boarding school, Bogor-Indonesia. Every student must be skilled in reading Arabic texts one of which is cognitive ability to read the contents of the reading. However, the method used is still traditional in which learning is only focused on the teacher’s direction. This research aims to improve the students’ ability to synthesize and evaluate an Arabic text. As a student of pesantren or Islamic Studies Programs, they must be able to understand the contents of the Arabic language text, one of which is the ability to synthesize and evaluate a text. In this study, the researchers conducted classroom action research to apply the reciprocal method in reading learning. The finding reveals that students’ reading Arabic skills in synthesizing and evaluating aspects experienced a significant increase. The average value in the pre-cycle was 57.1 then it rose to 68.7 in the first cycle. The average value increases in the second cycle, with 85.6. This proves that the right method in reading learning can help students improve their reading skills, one of which is the ability to synthesize and evaluate the contents of the reading.